2019
DOI: 10.1177/0300060519851656
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ischaemic conditioning on tissue oxygen saturation and heart rate variability: an observational study

Abstract: Objective Ischaemic conditioning (IC) has organ-protective effects, but its clinical results have been inconsistent. Tissue oxygen saturation (StO2) and heart rate variability (HRV) reflect peripheral microcirculation and autonomic nervous system activity, but their changes during IC have not been well documented. We assessed StO2 and HRV during IC in patients undergoing cardiac surgery and healthy volunteers. Methods Ten patients undergoing cardiac surgery and 10 healthy male volunteers underwent remote IC (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Interestingly, Chen and colleagues [31] studied subjects with "mild and stable" heart failure and found that a 6-week course of RIPC through BP cuff inflation/deflation on the upper arm improved clinical and virtually all HRV dependent markers though LF was decreased, HF was increased and the ratio therefore decreased, potentially due to alterations in PNS tone is subjects with heart failure [31]. In contrast, Cho and colleagues [32] found LF increased in healthy volunteers, but not in subjects undergoing cardiac surgery (HF was not reported). In summary, variability with regards to methods of induction of RIPC as well as target population have resulted in contradictory data as it pertains to changes in LF and HF variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Chen and colleagues [31] studied subjects with "mild and stable" heart failure and found that a 6-week course of RIPC through BP cuff inflation/deflation on the upper arm improved clinical and virtually all HRV dependent markers though LF was decreased, HF was increased and the ratio therefore decreased, potentially due to alterations in PNS tone is subjects with heart failure [31]. In contrast, Cho and colleagues [32] found LF increased in healthy volunteers, but not in subjects undergoing cardiac surgery (HF was not reported). In summary, variability with regards to methods of induction of RIPC as well as target population have resulted in contradictory data as it pertains to changes in LF and HF variables.…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on further elucidating the pathways involved in the NOB induced RIPC response by including both males and females and by focusing on the RIPC effects on heart rate variability (HRV) derived values. Prior studies with healthy subjects as well as patients with cardiovascular diseases have shown that various RIPC protocols are capable of eliciting changes in HRV derived parameters [25][26][27][28][29][30][31][32]. HRV is determined by measuring the beat-tobeat (RR) intervals and reflects cardiac autonomic modulation.…”
Section: Introductionmentioning
confidence: 99%